Population Response of Northern Bobwhite to Field Border Management Practices in Mississippi - Mark D. Smith; L. Wes Burger Jr. (National Quail Symposium Proceedings, 2017)
Empirical relationships of the intensity and spatial extent of field border management required to elicit measurable population responses of northern bobwhite are needed. We established 90.5km of herbaceous field borders (6.1 m wide) along row crop field edges on one half of each of 3 - 800-ha agricultural landscapes in northeast Mississippi. Mean percentage of row crop fields established in field borders was 6.0%. During 2000 - 2002, we measured breeding season abundance and fall density on all 3 sites and survival of radiomarked bobwhite on 2 of the 3 sites. We used space-use models of bobwhite habitat composition and configuration to estimate changes in habitat suitability resulting from field border implementation. Breeding season survival did not differ between bordered (S = 37.2, SE = 0.06) and non-bordered (S = 42.7, SE = 0.09; Χ1^2 = 0.001, P = 0.97) sites. Moreover, bordered and non-bordered sites did not differ significantly with respect to breeding season call counts (bordered = 1.0, SE = 0.18; non-bordered = 0.8, SE = 0.27; F1,10 = 0.44, P = 0.22) and fall density (bordered = 0.2 birds/ac, SE = 0.07; non-bordered = 0.1 birds/ac, SE = 0.05; F1,10 = 2.18, P = 0.17). However, field borders increased the amount of usable space on average up to 13.1% on bordered landscapes. The relatively low percentage of field borders established on our sites was not sufficient to elicit measurable population responses of bobwhite. We recommend at least 5-10% of a study area be placed in field border habitats to enhance local bobwhite populations.
Keywords: abundance; Colinus virginianus; habitat modeling; Mississippi; northern bobwhite; space use; suitability